Truncated staphylococcal nuclease is compact but disordered. - Flanagan, J M (1992)
Deletion of 13 amino acids from the carboxyl terminus of the 149-amino acid staphylococcal nuclease molecule results in a denatured, partly unfolded molecule that lacks persistent secondary structure but is compact under physiological conditions. Since the modification is a carboxyl-terminal deletion, it is argued that the state resembles a peptide emerging from the ribosome just before the complete folding pathway is initiated. In this paper, we characterize the molecule by nuclear magnetic resonance, circular dichroism, and small-angle x-ray scattering measurements. The truncated nuclease shows wild-type levels of activity in the presence of calcium and is found to fold into a native-like conformation in the presence of 3',5'-bisphospho-2'-deoxythymidine, a potent inhibitor. Thus, the truncated molecule retains the capacity to fold. Our results suggest that extensive solvent exclusion generates a compact polypeptide chain prior to the development of persistent secondary structural features as a protein folds during biosynthesis.